Boosting brand engagement and loyalty through gamified loyalty programmes (Revista Galega de Economía)
Gamification has emerged as a way of increasing conventional loyalty programmes effectiveness by promoting engagement. This study analyses whether gamified loyalty programme engagement transfers to a more enduring engagement and loyalty towards the brand. Using data from members of MyMcDonald’s Rewards, the results showed that customer engagement with the gamified loyalty programme promotes customer brand engagement, which subsequently favours brand loyalty and increases share-of-purchase and share-of-wallet.